Indian Mental Healthcare Act, 2017: CBR Matrix for Inclusive Implementation. (20th June 2018) - Sethi, Deepa
Abstract: India has witnessed a major shift from the predominant seclusion in the Indian Lunacy Act, 1912, when there was no effectiveness in the treatment provided, to the Mental Health Act, 1987, when the focus was on the treatment and care of mentally ill patients along with some efforts to de-stigmatize and ensure human rights, to the recent Mental Healthcare Act, 2017, which primarily focuses on the human rights of people with mental illness. This article analyses the Indian Healthcare Act, 2017, which was passed on April 7, 2017. The IMHA 2017 is a welcome Act after its predecessor Mental Health Act, 1987; however, it is not the ultimate solution. This article analyses the IMHA 2017, highlights the impediments in its implementation and suggests a win–win model for its implementation. A tailored version of CBR matrix is proposed for the inclusive implementation of the IMHA, 2017.